Legal Protection of Consumer Rights for Clean Water Services of Tirta Mulia Regional Public Company in Pemalang Regency - Ma’rufin, Muhammad Zainul; Subekti, Rahayu; Raharjo, Purwono Sungkowo (Strata International Journal of Social Issues, 2024)
This research examines the legal protection of consumers' rights to clean water services by the Regional Public Company (Perumda) Tirta Mulia, Pemalang Regency. The research background illustrates the importance of the availability of clean water as a basic human need in the context of Indonesian law, which is regulated by Law Number 8 of 1999 concerning Consumer Protection. The main focus of the research is to analyze how Perumda Tirta Mulia fulfills its obligations as a business actor in line with the Consumer Protection Law. In this context, research also identifies obstacles that may arise in protecting consumers legally, especially concerning clean water services. The method used is empirical legal research with a statutory and conceptual approach. Primary data was obtained through interviews with Perumda and consumers, while secondary data came from legal literature, statutory regulations, and related information sources. Data analysis was conducted qualitatively by referring to legal theories and consumer protection concepts. It is hoped that the results of this research can contribute to understanding the implementation of Law Number 8 of 1999 in the context of clean water services by Perumda. Apart from that, it is also hoped that this research can provide recommendations for increasing consumer legal protection and improving clean water services provided by Perumda Tirta Mulia, Pemalang Regency.